T cells for viral infections after allogeneic hematopoietic stem cell transplant - Bollard, Catherine M. (Blood, 2016)
Despite recent advances in the field of allogeneic hematopoietic stem cell transplantation (HSCT), viral infections are still a major complication during the period of immune suppression that follows the procedure. Adoptive transfer of donor-derived virus-specific cytotoxic T cells (VSTs) is a strategy to rapidly restore virus-specific immunity to prevent or treat viral diseases after HSCT. Early proof of principle studies demonstrated that the administration of donor-derived T cells specific for cytomegalovirus or Epstein-Barr virus (EBV) could effectively restore virus-specific immunity and control viral infections. Subsequent studies using different expansion or direct selection techniques have shown that donor-derived VSTs confer protection in vivo after adoptive transfer in 70% to 90% of recipients. Because a major cause of failure is lack of immunity to the infecting virus in a naïve donor, more recent studies have infused closely matched third-party VSTs and reported response rates of 60% to 70%. Current efforts have focused on broadening the applicability of this approach by: (1) extending the number of viral antigens being targeted, (2) simplifying manufacture, (3) exploring strategies for recipients of virus-naïve donor grafts, and (4) developing and optimizing “off the shelf” approaches.